Atravessamentos femininos na formação em Física em contexto de pandemia da Covid-19: um esboço cartográfico - Gomes, Marcelle Tácita de Oliveira (2023)
In this dissertation, I map the participation of women in the so-called exact sciences, in particular in Physics, in times of the covid-19 pandemic. Studies and daily practices show that there is an exclusion of diversities (gender, racial, social, ethical, political) in this field. The research was guided by the theories of Feminist Science and Gender Studies, studies supported by researchers such as Marcia Barbosa and Betina Lima (2013), Marinês Cordeiro (2017), Teresa de Lauretis (1987), Guacira Louro (1997), Margareth Rago (2013), Hilary Rose (1989), Steven Rose and Lisa Appignanesi (1989), Londa Schiebinger (2001), Carmen Silva and Silvia Camurça (2013), Fabiane Silva (2012) and Alessandra Alves (2021). Historically, in the process of development of science in Brazil, some social segments were markedly contemplated with the attraction of their members and women were not part of these segments. In this period of the covid-19 pandemic, the training process offered by federal universities in the country started to be carried out remotely. Most women begin to develop their academic training, in the exact sciences, within their homes. From this scenario, the research under development aims to map the intensities of these movements made by them during the pandemic, anchored in the thoughts of philosophers Deleuze and Guattari and authors Suely Rolnik (1989) and Virgínia Kastrup (2007). Guided by these authors, the research seeks to map these bodies, historically distanced from the field of exact sciences, and in the current singular moment of the covid-19 pandemic, bodies present and resistant in this space. In the sense of an exercise in intensity, we proposed to map, create, highlight, investigate, organize our ways of acting to think about the processes experienced in this pandemic period by women in training in a Physics course